HUBUNGAN ANTARA RASIO HUTANG DAN PROFITABILITAS DENGAN REAKSI PASAR (STUDI PADA PERUSAHAAN YANG MENGELUARKAN SUKUK) - Siti Ma'sumah (el-Jizya : Jurnal Ekonomi Islam, 2018)
Companies that will enlarge the business can issue sukuk to raise funds. Sukuk issuance by the company will be reacted by the market. The market reaction may be affected by the debt ratio and profitability. So of the research aims to determine the relationship between debt and profitability with market reaction. The population of this research is the company issuing the sukuk from 2007 to 2015. The sampling technique used in determining the sample is purposive sampling, with the following criteria: 1. The company is listed on the Indonesian Stock Exchange 2. Publish financial statements in the year of issuance of sukuk 3. Has the complete data needed in the study 4. Sukuk issued by the company in the same year been one that has the largest nominal. Based on the analysis that has been made known that the debt ratio does not significantly negative associated with market reaction. Profitability does not significantly positive associated with market reaction. Keywords: Debt Ratio, Profitability and Market Reaction.